PENGARUH KEPEMIMPINAN DAN PENGAWASAN TERHADAP KINERJA KARYAWAN PADA CV. RR MAJU MANDIRI KOTA LUBUKLINGGAU - Supriyanto Supriyanto; Syamsul Bahrun (Jurnal Media Ekonomi (JURMEK), 2017)
RR Maju Mandiri Lubuklinggau City is one of the distributor companies that do business in the field of chicken farming and broiler chicken distributor. The purpose of this study was to determine the effect of leadership and supervision on employee performance on CV. RR Maju Mandiri Lubuklinggau City. This type of research uses survey research methods with quantitative approaches. The results of the t test show that the supervision variables on the performance of CV employees. The Lubuklinggau City RR Advanced Mandiri value of t = 9.860 is greater than the ttable value of 2.021 with a significant level = 0,000 <(α) 0.05, df (n-2) 39 - 2 = 37 which is 2.021. The results of the F test show that the leadership and supervision variables on the performance of CV employees. Lubuklinggau City's RR Advanced Mandiri that the calculated F is 67.515> Ftable = 3.26 and the significance level simultaneously the significance is 0,000 <(α) = 0.05 df = n - k = 39 -2 - 1 = 36 is equal to 3, 26. Partially there is a significant influence between leadership on employee performance on CV. RR Maju Mandiri Lubuklinggau City this is because t count is = 8.167 with significant 0.000. while t table = 2.021. So thitung> Ftable then Ho is rejected and Ha is accepted. Partially there is a significant influence between leadership on employee performance on CV. RR Maju Mandiri Lubuklinggau City this is because t count = 9.860 with significant 0.000. while t table = 2.021. So thitung> Ftable then Ho is rejected and Ha is accepted. Taken together or simultaneously there is a significant influence between leadership and supervision on the performance of CV employees. RR Maju Mandiri Lubuklinggau City this is because Fcount is 67.515 with a significant 0.000. while Ftable = 3.26. So Fcount> Ftable then Ho is rejected and Ha is accepted.